Fonološke osobitosti Zbornika u Berčićevoj zbirci br. 5 i Fatevićeva zbornika duhovnoga štiva - Galić, Josip, filolog (Array, 2019)
In this paper, the phonological features of the Miscellany from Berčić Collection No. 5 (15th century) and the Fatević Miscellany of spiritual texts (1617) are analysed and mutually compared. In addition, the situation in both miscellanies is compared with the results of previous research of the phonological features of Croatian liturgical glagolitic texts and with the situation in other non-liturgical miscellanies. The analysis shows that mixing of the Church Slavonic and Croatian (Chakavian) elements is attested at the phonological level in both miscellanies, with Croatian (Chakavian) features being more frequent in both miscellanies, particularly in the younger Fatević’s Miscellany. The Ikavian-Ekavian reflex of jat with the prevalence of Ikavian examples and the change ę >a after ļ, which is preceded by the change of the root consonant cluster kl >kļ, provides a reliable indication that both miscellanies could have been written in the Zadar region, i.e. in the southern middle-Chakavian region.